One-year longitudinal study of psychological distress and self-assessed health in survivors of out-of-hospital cardiac arrest. Issue 7 (3rd July 2019) - Viktorisson, Adam; Sunnerhagen, Katharina S; Johansson, Dongni; Herlitz, Johan; Axelsson, Åsa
Abstract : Objectives: Few studies have investigated the psychological and health-related outcome after out-of-hospital cardiac arrest (OHCA) over time. This longitudinal study aims to evaluate psychological distress in terms of anxiety and depression, self-assessed health and predictors of these outcomes in survivors of OHCA, 3 and 12 months after resuscitation. Methods: Recruitment took place from 2008 to 2011 and survivors of OHCA were identified through the national Swedish Cardiopulmonary Resuscitation Registry. Inclusion criteria were age ≥18 years, survival ≥12 months and a Cerebral Performance Category score ≤2. Questionnaires containing the Hospital Anxiety and Depression Scale and European Quality of Life 5 Dimensions 3 Level (EQ-5D-3L) were administered at 3 and 12 months after the OHCA. Participants were also asked to report treatment-requiring comorbidities. Results: Of 298 survivors, 85 (29%) were eligible for this study and 74 (25%) responded. Clinically relevant anxiety was reported by 22 survivors at 3 months and by 17 at 12 months, while clinical depression was reported by 10 at 3 months and 4 at 12 months. The mean EQ-5D-3L index value increased from 0.82 (±0.26) to 0.88 (±0.15) over time. There were significantly less symptoms of psychological distress (p=0.01) and better self-assessed health (p=0.003) at 12 months. Treatment-requiring comorbidity predicted anxiety (OR 4.07, p=0.04), while being female and young age predicted poor health (OR 6.33, p=0.04; OR 0.91, p=0.002) at 3 months. At 12 months, being female was linked to anxiety (OR 9.23, p=0.01) and depression (OR 14.78, p=0.002), while young age predicted poor health (OR 0.93, p=0.003). Conclusion: The level of psychological distress and self-assessed health improves among survivors of OHCA between 3 and 12 months after resuscitation. Higher levels of psychological distress can be expected among female survivors and those with comorbidity, while survivors of young age and who are female are at greater risk of poor health.